2000
DOI: 10.1054/bjoc.2000.1201
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: The receptor for epidermal growth factor (EGF) is a transmembrane glycoprotein with intrinsic tyrosine kinase activity (Ullrich and Schlessinger, 1990). Many human cancers of epithelial origin express high numbers of EGF receptors and are stimulated by activation of the receptor via a transforming growth factor-α (TGF-α)/EGF receptor autocrine loop (Ozanne et al, 1986;Cowley et al, 1986;Ishitoya et al, 1989;Hendler and Ozanne, 1984). The increased receptor levels are associated with poor clinical prognosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We measured apoptosis using an enzyme-linked immunosorbent assay (ELISA) kit (Roche Diagnostics Corp., Indianapolis, IN) that quantitatively measures cytoplasmic histone-associated DNA fragments (mononucleosomes and oligonucleosomes) and by Western blotting with an antibody that recognizes both uncleaved and cleaved PARP after various treatments, as previously described [43] , [44] .…”
Section: Methodsmentioning
confidence: 99%
“…We measured apoptosis using an enzyme-linked immunosorbent assay (ELISA) kit (Roche Diagnostics Corp., Indianapolis, IN) that quantitatively measures cytoplasmic histone-associated DNA fragments (mononucleosomes and oligonucleosomes) and by Western blotting with an antibody that recognizes both uncleaved and cleaved PARP after various treatments, as previously described [43] , [44] .…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cells with high expression of EGFR are often accompanied by a significant increase in the level of pro-angiogenic factors, resulting in increased angiogenesis. Cetuximab can significantly inhibit the expression of pro-angiogenic factors, thereby reducing tumor angiogenesis ( 21 23 ); (f). Cetuximab or other similar anti-EGFR antibody treatments alter Bcl-2 (anti-apoptosis) and Bax (pro-apoptosis) protein balance, promoting apoptosis in tumor cells ( 23 , 24 ); (g).…”
Section: Anti-tumor Mechanisms and Effects Of Egfr Mabsmentioning
confidence: 99%
“…Cetuximab can significantly inhibit the expression of pro-angiogenic factors, thereby reducing tumor angiogenesis ( 21 23 ); (f). Cetuximab or other similar anti-EGFR antibody treatments alter Bcl-2 (anti-apoptosis) and Bax (pro-apoptosis) protein balance, promoting apoptosis in tumor cells ( 23 , 24 ); (g). In a recent study, cetuximab was shown to induce radiosensitization of A549 cells by increasing H2AX (H2A histone family, member X) levels and inhibiting DNA-pk ( 25 ).…”
Section: Anti-tumor Mechanisms and Effects Of Egfr Mabsmentioning
confidence: 99%
“…Our results are in line with a former study which reported that cetuximab induced DNA fragmentation and caspase-3 activation in WT colon cancer cells. [33] In addition, apoptotic cell death was not detected in HCT-116 or HT-29 cell lines treated with panitumumab or cetuximab as mono-treatments. [34] As previously reported, anti-EGFR inhibitors reduce the phosphorylated level of Akt [35] and increase the level of cleaved caspase-3, inducing apoptotic cell death.…”
Section: Gene Forward Primer Backword Primer Referencementioning
confidence: 95%